2015
DOI: 10.1007/s10482-015-0579-z
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus bulliens sp. nov., a novel lactic acid bacterium isolated from camel milk

Abstract: Four lactic acid bacteria isolates obtained from fresh dromedary camel milk produced in Dakhla, a city in southern Morocco, were characterised in order to determine their taxonomic position. The four isolates had highly similar MALDI-TOF MS and RAPD fingerprints and identical 16S rRNA gene sequences. Comparative sequence analysis revealed that the 16S rRNA gene sequence of the four isolates was most similar to that of Enterococcus sulfureus ATCC 49903(T) and Enterococcus italicus DSM 15952(T) (99.33 and 98.59%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The tree was constructed using MEGA7 with 1000 bootstrap italicus and E. bulliens, which were identified in fresh camel milk. 21 Enterococcus spp. have been isolated all over the world, for example in China E. faecalis, E. faecium and E. hirae were isolated in fresh goat milk.…”
Section: Discussionmentioning
confidence: 99%
“…The tree was constructed using MEGA7 with 1000 bootstrap italicus and E. bulliens, which were identified in fresh camel milk. 21 Enterococcus spp. have been isolated all over the world, for example in China E. faecalis, E. faecium and E. hirae were isolated in fresh goat milk.…”
Section: Discussionmentioning
confidence: 99%
“…Enterococci are Gram-positive cocci that occur in pairs or short chains, nonspore forming, catalase and oxidase-negative, and facultative anaerobic [6, 7]. The genus Enterococcus belongs to lactic acid bacteria (LAB) and represents the third-largest LAB genus after Lactobacillus and Streptococcus with 37 species classified based on phylogenetic assessment using 16S rRNA sequencing and DNA-DNA hybridisation [3].…”
Section: General Characteristics Of Enterococcimentioning
confidence: 99%
“…The prevalence of enterococci in milk has been traditionally considered as a result of faecal contamination, but many studies have reported that this occurrence is not always related to faecal contamination [7, 23, 24]. In fact, Enterococcus spp.…”
Section: General Characteristics Of Enterococcimentioning
confidence: 99%
See 1 more Smart Citation
“…The few published studies on its microbiota have shown that, like other milks, camel milk is a source of lactic acid bacteria, primarily lactobacilli, lactococci, and enterococci (Quigley et al, 2013; Kadri et al, 2015). Nevertheless, differences in the composition of camel milk compared to cow milk (Farah, 1993; Ochirkhuyag et al, 1998; Konuspayeva et al, 2007) and the desert environment away from anthropogenic pressure could underlie significant differences in its microbial ecosystem and the biological characteristics thereof.…”
Section: Introductionmentioning
confidence: 99%